PREDIKTOR SYMPTOMATIC INTRACEREBRAL HEMORRHAGE PASCATROMBOLISIS INTRAVENA PADA STROKE ISKEMIK AKUT - Al Rasyid,* Salim Harris,* Mohammad Kurniawan,* Rakhmad Hidayat,* Taufik Mesiano* (NEURONA, 2018)
ITS EFFECTIVENESS THE PERCENTAGE OF ISCHEMIC STROKE PATIENTS WHO RECEIVED DEFINITIVE TREATMENT THROMBOLYSIS NEVER WENT ABOVE 10 DUE TO ONE OF THE REASON IS THE OCCURRENCE OF SEVERE POSTTHERAPEUTIC COMPLICATIONS SUCH AS SYMPTOMATIC INTRACEREBRAL HEMORRHAGE SICH SEVERAL FACTORS CONTRIBUTE TO SICH OCCURRENCE ARE AGE SEVERITY OF STROKE EARLY CHANGES OF ISCHEMIC SIGN HYPERGLYCEMIA BLOOD PRESSURE ANTIPLATELET USE AND ITS INTERVAL